Incidence of Toxoplasmosis in Psoriasis Patients and Possible Correlation with Tumor Necrosis Factor-α - Entsar J. Saheb; Yasser A.H Al-Issa; Israa Salim Mussa; Khawla H. Zghair (مجلة بغداد للعلوم)
Toxoplasma gondii is an opportunistic parasite in immune-compromised persons. The prevalence of toxoplasmosis in psoriasis patients is investigated. In addition, the treatment effect on psoriasis patients infected with toxoplasmosis through evaluating Tumor Necrosis Factor-α (TNF-α) cytokine levels is studied. Blood samples were collected from 130 individuals who involved 60 control samples and 70 samples with psoriasis. They attended Medical City Hospital in Baghdad province from October 2017 - February 2018. Then, the anti- T. gondii antibodies (IgM and IgG) and TNF- α in the sera were determined via the enzyme linked immune-sorbent assay. The highest rate of anti-Toxoplasma IgG was in psoriasis patients before treatment, it was 45 (64.29%) compared with the control which was 33 (55.00%), while the highest sero-positive rate of T. gondii IgM in the control group was 14 (23.33%) compared with patients with psoriasis 10 (14.29%). The highest rate of toxoplasmosis was in the age group (21-30) years in psoriasis patients which was 14 (31.82%). In addition, the TNF- α levels in psoriatic patients before treatment were 180.2±2.2 µg/ml, and after treatment were 223.3±41.1 µg/ml compared with the healthy control group 90.5±1.9 µg/ml. These findings suggest that incidental rate of toxoplasmosis is higher in psoriasis patients. Thus, the incidental rate of toxoplasmosis could be considered as an indication to the high risk of psoriasis.